## Solving the Equation: 0.3(8-3x) = 3.2 - 0.8(x-7)

This article will guide you through the steps of solving the linear equation **0.3(8-3x) = 3.2 - 0.8(x-7)**. Let's break down the process:

### Step 1: Distribute

**Left side:**Multiply 0.3 by both terms inside the parenthesis:- 0.3 * 8 = 2.4
- 0.3 * -3x = -0.9x

**Right side:**Multiply -0.8 by both terms inside the parenthesis:- -0.8 * x = -0.8x
- -0.8 * -7 = 5.6

Now the equation becomes: **2.4 - 0.9x = 3.2 - 0.8x + 5.6**

### Step 2: Combine Like Terms

**Right side:**Combine the constant terms: 3.2 + 5.6 = 8.8

The equation is now: **2.4 - 0.9x = 8.8 - 0.8x**

### Step 3: Isolate the x terms

- Add 0.9x to both sides: 2.4 - 0.9x + 0.9x = 8.8 - 0.8x + 0.9x
- This simplifies to:
**2.4 = 8.8 + 0.1x**

### Step 4: Isolate the Constant Terms

- Subtract 8.8 from both sides: 2.4 - 8.8 = 8.8 + 0.1x - 8.8
- This simplifies to:
**-6.4 = 0.1x**

### Step 5: Solve for x

- Divide both sides by 0.1: -6.4 / 0.1 = 0.1x / 0.1
- This results in:
**x = -64**

### Solution

Therefore, the solution to the equation **0.3(8-3x) = 3.2 - 0.8(x-7)** is **x = -64**.